2016
DOI: 10.1371/journal.pone.0152388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mRNA Biomarkers to Identify Risk of Hospital Acquired Infections in Children Admitted to Paediatric Intensive Care Unit

Abstract: ObjectivesHospital-acquired infections (HAI) are associated with significant mortality and morbidity and prolongation of hospital stay, adding strain on limited hospital resources. Despite stringent infection control practices some children remain at high risk of developing HAI. The development of biomarkers which could identify these patients would be useful. In this study our objective was to evaluate mRNA candidate biomarkers for HAI prediction in a pediatric intensive care unit.DesignSerial blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…At the same time, children who later developed a secondary acquired infection had higher plasma cytokine concentrations (i.e., IL-6, IL-8, and TNF-α). This is in agreement with observations from genomic studies that have found that early mRNA expression modulations of cytokines and apoptotic genes were associated with deleterious outcomes (mortality, secondary infections) [ 29 , 30 ]. Moreover, to the best of our knowledge, this is the first pediatric study which reported correlation between initial cytokine storm and alteration of innate immunity, represented by loss of mHLA-DR.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, children who later developed a secondary acquired infection had higher plasma cytokine concentrations (i.e., IL-6, IL-8, and TNF-α). This is in agreement with observations from genomic studies that have found that early mRNA expression modulations of cytokines and apoptotic genes were associated with deleterious outcomes (mortality, secondary infections) [ 29 , 30 ]. Moreover, to the best of our knowledge, this is the first pediatric study which reported correlation between initial cytokine storm and alteration of innate immunity, represented by loss of mHLA-DR.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that surgical patients were more liable to HAI than medical and septic patients, but in previous studies, the risk was equal, with a minimal increase in complications in septic patients [ 12 , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 62%
“…In previous studies, HAI rate ranged from 30% to 55% and pneumonia was the most common HAI. Blood culture positive results ranged from 35% to 55%, the most commonly isolated species were: Klebsiella pneumoniae , Pseudomonas, Acinetobacter, and Staphylococcus aureus [ 12 , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work done to address the challenge of effective prediction of nosocomial infections. Several techniques using rule-based approaches [18–20], Bayesian Networks [10, 21], Ontologies [22], landmark competing risk prediction models [23], statistical models [2427], case based reasoning [28, 29], and others [3033] have been suggested and implemented in the past. The problem of identifying new, unanticipated, and useful patterns in public health surveillance and hospital infection control data is discussed in [19].…”
Section: Introductionmentioning
confidence: 99%